Emotional Components of Pain - Carla J Hale; Thomas Hadjistavropoulos (Pain Research and Management)
BACKGROUND: Current definitions of pain suggest that emotion is an essential component of pain, however, the presumed relationship between emotion and pain, and the specific emotions that are involved in pain experiences have yet to be clarified.